EFFECT OF LIGHT PERCENTAGE GIBBERELLIC ACID CONCENTRATIONS AND SPRAYING DATES ON GROWTH OF - Mudhafar O. Abdullah (Mesopotamia Journal of Agriculture)
This study has been carried out in the nursery of Forestry Department.College of Agriculture and Forestry in location of Mosul University. during the period from the beginning of February till the end of December, to investigate the effect of different light percentage, Gibberellic Acid concentrations and its spraying dates in spring and fall on some growth characters of Pinus halepensis Mill. Seedlings.The following characters have been studied : Survival percentage, Main stem length, Main stem diameter, Number of branches per seedling, Main root length, Main root diameter. The results can be summarized as follows: 1. There is a significant effect of light percentage on characters and light percentage ( %) caused significant increase in all character means . 2. Plant spraying with ( 60 mg/L) of gibberellic acid caused significant increase characters means except survival percentage . 3. Gibberellic Acid spraying in spring and fall caused significant increase in characters . 4. The best triple interactions which caused increase in all character means in Spraying of Gibberellic Acid at concentration of ( 60 mg / L ) at two dates with light percentage ( 25%) .